The challenges to library learning [ solutions for librarians - Massis, Bruce E. (Routledge studies in library and information science, 2008)
Offers a practical philosophy of engagement that can be used to meet the challenges facing librarians, including staffing shortages, depleted or eliminated training budgets, longer hours, greater